Female Labour Migration in India : Insights From NSSO Data - K.Shanthi (MADRAS SCHOOL OF ECONOMICS, 2006)
The objective of this working paper is to examine the extent of employment oriented migration of females in India and the inter -state variations in its magnitude using NSSO 55th Round Household level data on Migration . It is found that though the percentage is very small for `employment oriented migration' an analysis of work force participation of female migrants in the age group 15-60 , irrespective of the reasons for migration reveals that in the post migration period work participation of these migrants increases steeply in all the states. Though marriage is identified as the reason for migration they work prior to and after migration which is not brought to limelight. In the recent past `independent migration' of females is on the increase in response to the employment opportunities in export industries, electronic assembling and garment units. The extent of this independent migration is arrived at indirectly using proxy variables such as the `never married' category among the migrants and those who identified themselves as `heads'. In all the states in South India this percentage is high .In the north at the disaggregated level the percentage of `never married' and "heads" is high in rural urban and urban -urban migration . The issues and challenges to be faced are highlighted and this paper concludes that gender dimensions should adequately be captured in the official data system for purposes of effective policy interventions